Physician Parents Attending Work Despite Own Sick Children: A Qualitative Study on Caregiver Presenteeism Among Norwegian Hospital Physicians - Lise Tevik Løvseth; Fay Giaever (SAGE Publishing, 2018)
Background: Studies have shown that physicians manifest a clear duty to work, even in the face of personal risk, and despite their own symptoms of ill health; this is termed presenteeism. We lack knowledge on their willingness to attend work when their children are sick or in times of concern for their unborn; this is termed caregiver presenteeism . To gain a comprehensive knowledge on the occurrence of presenteeism among physicians, it is important to include caregiver presenteeism. Objective: The aim of this study is to explore the perception and experience with caregiver presenteeism among hospital physicians who are parents or pregnant and to explore its foundations and its consequences. Methods: Secondary thematic analysis of semi-structured interviews of hospital physicians (N = 18). Results: Positive and negative dimensions associated with (1) situations with severe pregnancy symptoms or responsibility for sick children; (2) the perceived impact on their work commitments, personal health, and adequate care for own children; (3) accompanying moderators in the organisational structure and professional culture; and (4) proposed approaches to resolve caregiver and work responsibilities simultaneously contributing to caregiver presenteeism. Conclusions: The study underlines the impact of factors in organisational structure, professional culture, and the personal sphere affecting caregiver presenteeism. It appears that targeting factors contributing to attendance pressure in physicians, including those who are pregnant, is particularly important. This includes changing attitudes towards caregiver responsibilities among physician colleagues, department leaders, and physicians themselves, as well as simple cost-efficient organisational interventions in staffing, routines of absence, and work adjustment.